Źródła finansowania a strumienie przepływów pieniężnych w towarowych gospodarstwach rolniczych - Mądra, Magdalena (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2011)
The elaboration presents the debt level in relation to cash flow management in agriculture farms. The article deals also with statistical correlation between the level of liabilities in equity and cash flow indicators. The presented research was surveyed in years 2004–2007, in Mazowsze and Podlasie region. Farms have been characterized by criterion of an agriculture type and an economic power (ESU) according to acknowledged classification of PL-FADN. The operational cash flow surplus index was the highest in farms which did not posses any debt, however this ratio recorded decreasing level in group with the highest participation of liabilities in total assets. This relation explained the attitude of conservative farmers to the debt capital engagement. According to Spearman correlation index farmers minimized the debt participation in their assets in relation to an increasing level of operational cash balance.